Character Education Strategy Through Example and Habitation - Awalul Maratussholihah; Ari Wibowo (Profesi Pendidikan Dasar, 2022)
This study aimed to describe the strategy of character education through example and habituation at an elementary school in Kulon Progo. A qualitative method was used, data was collected through observation, interviews and documentation techniques. The sources of data were obtained from the Principal, Class I Teachers, Class IV Teachers, Class I Students, and Class IV Students. The data analysis technique used was the Miles and Huberman model. The results indicated that the character values at the elementary school in Kulon Progo included religious character values, care for the environment, love for the homeland, discipline, and responsibility. The SCE program was implemented in three stages: planning, which was integrated into the curriculum, syllabus, and lesson plans; implementation, which was done through example and habituation, using routine activities, spontaneous activities, and programmed activities; and evaluation, which was carried out on a weekly or monthly basis through official meetings. Barriers to the implementation of the SCE program included the different characters of students and the lack of cooperation from various parties. Solutions to overcome these obstacles included reminding students, providing examples, increasing cooperation, and communicating more about student behavior.